2020
DOI: 10.1007/1345_2020_101
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Lesser Antilles Vertical Velocity Fields Using a GNSS-PPP Software Comparison

Abstract: Vertical land motion in insular areas is a crucial parameter to estimate the relative sealevel variations which impact coastal populations and activities. In subduction zones, it is also a relevant proxy to estimate the locking state of the plate interface. This motion can be measured using Global Navigation Satellite Systems (GNSS), such as the Global Positioning System (GPS). However, the influence of the processing software and the geodetic products (orbits and clock offsets) used for the solution remains b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…The islands of Guadeloupe and Martinique, for which station density is highest, show subsidence rates from 0 ± 0.3 to 3.8 ± 0.9 mm/yr (Fig. 2b), in good agreement with a recent study by Sakic et al (2020) who found similar vertical velocities from two independent geodetic solutions (Supporting Information Fig. S1 and Table S3).…”
Section: O B S E Rv E D V E Rt I C a L M O T I O N Ssupporting
confidence: 89%
See 2 more Smart Citations
“…The islands of Guadeloupe and Martinique, for which station density is highest, show subsidence rates from 0 ± 0.3 to 3.8 ± 0.9 mm/yr (Fig. 2b), in good agreement with a recent study by Sakic et al (2020) who found similar vertical velocities from two independent geodetic solutions (Supporting Information Fig. S1 and Table S3).…”
Section: O B S E Rv E D V E Rt I C a L M O T I O N Ssupporting
confidence: 89%
“…Panels on the right show comparisons between different solutions (b-d) where the dashed line indicates the diagonal on which velocities would plot if they are equal in magnitude between solutions. The comparison with the two solutions of Sakic et al (2020) shows a good agreement with the one presented here, with subsidence at most common sites at rates that are consistent within uncertainties. Differences between our solution and those of Sakic et al (2020) likely stem from the duration of the time-series used (longer in our analysis), the fact that they use a PPP approach versus a network strategy, as well as a different implementation of the ITRF14 reference frame.…”
Section: Data Ava I L a B I L I T Ysupporting
confidence: 81%
See 1 more Smart Citation
“…show a general pattern of subsidence of the Lesser Antilles, while islands at the edges of the subduction (i.e., the Virgin Islands in the North and Trinidad in the South) show uplift. The islands of Guadeloupe and Martinique, for which station density is highest, show subsidence rates between 0 ± 0.3 to 3.8 ± 0.9 mm/yr (Figure 2B), in good agreement with a recent study by Sakic et al (2020) who found similar vertical velocities from two independent geodetic solutions. The variability likely results from local site conditions, but mostly from variations in time series duration amongst GNSS stations.…”
Section: Vertical Gnss Confirms Uncoupled Subduction Interfacesupporting
confidence: 90%